Influences of student race/ethnicity and gender on autism special education classification considerations. (August 2022) - Golson, Megan E; Haverkamp, Cassity R; McClain, Maryellen Brunson; Schwartz, Sarah E; Ha, Jennifer; Harris, Bryn; Benallie, Kandice J
Although the prevalence of autism continues to rise, identification disparities across race/ethnicity and gender persist in schools. The under- and overidentification of specific populations receiving special education services under the classification of autism contribute to misappropriation or lack of intervention services for students. Practicing school psychologists ( N  = 229) reviewed one of eight vignettes depicting a student displaying possible autism symptoms that varied only by student race/ethnicity and gender. Afterward, they rated the likelihood that they would consider the classification of autism and their confidence in that likelihood rating. School psychologists were more likely to consider an autism classification for Asian female students than Latinx female students. Confidence in likelihood ratings was higher for Asian students than Black students. School psychologists endorsed specific attention to student problem behaviors with minimal notice of possible contributing cultural and linguistic factors. The results highlight that potential implicit biases and lack of cultural consideration play a role in the identification of autism in schools, which may contribute to the nationally documented race/ethnicity and gender identification disparities. Lay Abstract: Autism prevalence has continued to rise in recent years. However, females and children from Black, Latinx, and Asian backgrounds are often misidentified or identified less often than White males. These identification disparities make it difficult for children to receive appropriate special education and school intervention services. In this study, school psychologists read a vignette featuring a student with possible autism symptoms. The vignette varied by student race/ethnicity and gender. Afterward, participants rated the likelihood that they would classify the student with autism and their confidence in this rating. Student race/ethnicity and gender influenced both classification likelihood and confidence. These results suggest that school psychologists are influenced by implicit bias and do not fully consider cultural factors in school autism evaluations. This may contribute to identification disparities.